Lasso peptides : bacterial strategies to make and maintain bioactive entangled scaffolds /: bacterial strategies to make and maintain bioactive entangled scaffolds. (2015) - Li, Yanyan; Zirah, Séverine; Rebuffat, Sylvie
No abstract available